Моделювання плазмонних властивостей частинок моносульфіду міді в ближньому ІЧ діапазоні - Мельников, С.; Булавінець, Т.; Стахіра, П.; Яремчук, І.; Melnykov, S.; Bulavinets, T.; Stakhira, P.; Yaremchuk, I. (Видавництво Львівської політехніки, 2023)
Теоретично досліджено спектри екстинкції частинок моносульфіду міді в умовах локалізованого поверхневого плазмонного резонансу. Дослідження здійснено для плазмонних частинок моносульфіду міді сферичної та еліпсоїдної форми змінного розміру в середовищах із різними значеннями показника заломлення. Показано, що відхилення від сферичності частинок впливатиме як на положення максимуму екстинкції на спектральній шкалі, так і на форму спектральної кривої. Збільшення співвідношення довжин півосей еліпсоїда призводить до істотного зростання амплітуди піка екстинкції та його зміщення у довгохвильову область. Частинки моносульфіду міді еліпсоїдної форми демонструють покращені характеристики поверхневого плазмона порівняно зі сферичними та можуть ефективно використовуватися у ближній інфрачервоній області спектра.

This paper is devoted to the theoretical study of the extinction spectra of copper monosulfide particles under conditions of localized surface plasmon resonance. The study was conducted for plasmonic copper monosulfide particles of spherical and ellipsoidal shapes of variable size in media with different values of the refractive index. The simulation results reveal that increasing the radius of CuS nanoparticles leads to a significant enhancement in the amplitude of the plasmon peak and a shift of the peak towards longer wavelengths. It was investigated how the positions of the extinction peaks on the spectral scale and their amplitudes change when the particles deviate from the spherical shape. Simulations were performed for spherical and elongated ellipsoidal particles with fixed cross-sectional radius and variable length. Specifically, we varied the length of the major axis while keeping the lengths of the minor axes constant. It is shown that the deviation from the sphericity of the particles will affect both the position of the extinction maximum on the spectral scale and the shape of the spectral curve. An increase in the ratio of the ellipsoid semi-axes lengths leads to a significant increase in the amplitude of the extinction peak and its shift to the long-wavelength region. Besides, the position of the plasmonic peak on the spectral scale is influenced not only by the geometric parameters of the particles such as size and shape but also by the dielectric properties of the surrounding medium, including its refractive index. We assess the impact of changing the refractive index of the surrounding medium on the shape, amplitude, and position of the extinction maxima of CuS nanoparticles. It is showed that increasing the refractive index of the surrounding medium leads to a significant shift of the plasmon resonance peak into the long-wavelength region of the spectrum an increase in the peak width, and a decrease in its amplitude. Thus, ellipsoid copper monosulfide particles show improved surface plasmon characteristics compared to spherical ones and can be effectively used in the near-infrared spectral region.
Simulation of plasmon properties of copper monosulphide particles in the NIR range
Keywords: моносульфід міді; локалізований поверхневий плазмонний резонанс; спектри екстинкції; сферичні частинки; еліпсоїдні частинки; CuS; взаємодія плазмонних частинок із електромагнітним випромінюванням; copper monosulfide; localized surface plasmon resonance; extinction spectra; spherical particles; ellipsoidal particles; CuS; interaction of plasmonic particles with electromagnetic radiation; 53.072; 53; 004